A Descriptive Study Of Stress Level, Sleep Quality, And Physical Activity Of Final Students - Muhammad Akbar Syafruddin; Alif Aryadi Hardi (PT Mediatama Zayna Indonesia, 2026)
This study aimed to examine the levels of stress, sleep quality, and physical activity among final-year students of the Physical Education, Health, and Recreation Study Program, Faculty of Sports and Health Sciences, State University of Makassar. A descriptive quantitative research design was employed, involving 70 students selected through a random sampling technique. Data were collected using closed-ended questionnaires, including a Likert-scale questionnaire to measure stress levels, the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality, and the International Physical Activity Questionnaire (IPAQ) to evaluate physical activity levels. The findings revealed that the majority of students demonstrated good levels of stress management (47.1% or 33 students), sleep quality (48.6% or 34 students), and physical activity (41.4% or 29 students). Descriptive statistical analysis showed the following mean scores and standard deviations: stress (M = 82.56; SD = 8.237), sleep quality (M = 82.86; SD = 8.058), and physical activity (M = 82.24; SD = 8.423). Although the overall results indicate that students generally fall within the good category across these variables, several aspects still require improvement. Therefore, it can be concluded that the levels of stress, sleep quality, and physical activity among final-year students are generally categorized as good, although they have not yet reached an optimal condition overall.